Recent Advancements in Biomimetic 3D Printing Materials With Enhanced Mechanical Properties - Yan, Xinxin; Bethers, Brandon; Chen, Hengxi; Xiao, Siqi; Lin, Shuang; Tran, Brian; Jiang, Laiming; Yang, Yang (Frontiers in Materials, 2021)
Nature has developed a wide range of functional microstructures with optimized mechanical properties over millions of years of evolution. Biomimicry, by learning from nature’s excellent models and principles, is providing a practicable strategy for designing and fabricating the next smart materials with enhanced properties. Nevertheless, the complicated micro-structural architectures in nature models exceed the capability of traditional processes, hindering the developments of biomimetic research and its forthputting in engineering systems. Additive manufacturing (AM) or 3D printing process has revolutionized the manufacturing world through its freedom of design, mass customization, waste minimization, and ability to manufacture complex micro/mesostructures, as well as fast prototyping. Here, an overview of recent developments in biomimetic 3D printing materials with Enhanced mechanical properties is provided. The design and fabrication inspired are from various creatures, such as lobster claw, honeycomb, nacre, balsa wood, etc., are present and discussed. Finally, future challenges and perspectives are given.